Pengaruh Sosialisasi Perpajakan, Layanan Fiskus Dan Tarif Pajak Terhadap Kepatuhan Wajib Pajak UMKM Di KPP Pratama Batam Selatan - Tini; Dian Wahyudin (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The contribution of tax to state revenue is currently the largest. Therefore, absolute tax compliance is needed from Taxpayers so that state expenditure is not disrupted. This study examines how Tax Socialization, Fiscus Services and Tax Rates play a role in increasing Taxpayer compliance. The data collection method in this study is a questionnaire survey distributed through the Google Form platform to respondents in the working area of ​​the South Batam Pratama Tax Office. Non-probability sampling with the purposive sampling method was used as a sampling technique. Data were collected from November 2024 to December 2024. The sample in this study was 100 MSME Taxpayer respondents from a total population of 3,811 MSME Taxpayers registered at the South Batam Pratama Tax Office. Through multiple linear regression tests and coefficient difference tests, the results of this study indicate that Tax Socialization has an effect on tax compliance of MSME Taxpayers at KPP Pratama Batam Selatan by 52.4%, Fiscus Services by 51.7% and Tax Rates by 38.3%. Simultaneously, these three variables have an effect on the level of compliance of MSME Taxpayers at KPP Pratama Batam Selatan by 62.4%.